Politics in the media and the media in politics: A comparative study of the relationship between the media and political systems in three European countries - Ciaglia, Antonio (European Journal of Communication, 2013)
The link between mass media systems and politics is widely acknowledged and has been confirmed by a significant amount of research. However, the degree of this tie and the forms that it can take vary significantly according to different national contexts. By conducting a comparative analysis that is centred on three cases in the United Kingdom, Germany and Italy, this study addresses the overlap between media and politics from a dual perspective: the politicization of public service broadcasting and the permeability of the political system for media-related personalities or practitioners. The data show that the natural connection between political and media systems is never completely absent, although profound differences can be detected in the extent and in the implications that these connections can have for the entire system.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjY3MzIzMTEzNDk0ODgy